Evaluasi Penerapan Teknik Crashing dalam Manajemen Waktu Pembangunan Rumah Subsidi Metode CPM Dan PERT (Studi Kasus Rumah Pondok Alam Desa Sigara-Gara) - Purnomo, Khalid Bima; Ardan, Melloukey (Portal: Jurnal Teknik Sipil, 2025)
Project scheduling is a key element in construction planning, aimed at determining the project execution timeline based on the sequence of activities from start to finish within the set time frame. This study utilizes the Critical Path Method (CPM) and the Project Evaluation and Review Technique (PERT) to address the scheduling challenges in the housing construction project. The primary objective of this research is to identify the critical paths within the project and evaluate the project duration, using the CPM approach and crashing technique to accelerate the completion of activities on the critical path. The primary data used includes S-curves, bar charts, and direct data from the implementer of the Pondok Alam Sigara-Gara housing project. The research results indicate two critical paths in the project, namely path A - E - F - G - M - N - P - Q and path B - C - D - I. Using the CPM method, the original project duration of 30 days can be reduced to 25 days. The application of PERT with crashing shows varying results: a 1-day acceleration results in a duration of 22 days with an additional cost of IDR 11,280,000, a 2-day acceleration results in a duration of 21 days with an additional cost of IDR 14,100,000, and a 3-day acceleration results in a duration of 22 days with an additional cost of IDR 12,690,000. The analysis results demonstrate that increasing the workforce is more cost-effective than overtime in terms of both cost efficiency and project duration.